Cognition-oriented treatments and physical exercise on cognitive function in Huntington's disease: protocol for systematic review. (4th March 2022) - Huynh, Katharine; Nategh, Leila; Jamadar, Sharna; Georgiou-Karistianis, Nellie; Lampit, Amit
Abstract: Introduction: Cognitive impairments are prevalent in Huntington's disease (HD), occurring many years prior to clinical diagnosis and are the most impactful on quality of life. Cognitive interventions and exercise have been found to be efficacious in improving cognitive function in several clinical populations (e.g. older adults with mild cognitive impairment and dementia). However, the utility of cognitive interventions has not been systematically reviewed in HD. This systematic review aims to examine the efficacy of cognitive and physical interventions on cognitive function in HD. Methods: Electronic databases (MEDLINE, EMBASE, PsycINFO, CENTRAL) were searched from inception until 10 May 2021 for interventional studies investigating the effect of cognition-oriented treatments and physical exercise on cognitive function in individuals with HD, compared to any control or no control. The primary outcome is change on objective measures of cognition. Additional outcomes include change in psychosocial, functional and neuroimaging measures. Variations of effects based on population and study factors will be considered. Risk of bias will be assessed using the Cochrane RoB 2 tool and ROBINS-I tool. Where appropriate, outcomes will be pooled using random-effects meta-analyses, heterogeneity will be examined using tau 2 and I 2 statistics, and moderators will be examined using meta-regression models. Discussion: This review will systematically evaluate the efficacy of cognitive and physical interventions on improving cognitive function in HD. The eligibility criteria and planned analyses will allow for a comprehensive assessment of certainty in the evidence that will inform future trials and clinical practice. Registration: This protocol was registered on PROSPERO (CRD42021259152).